2010
DOI: 10.1590/s1519-69842010005000013
|View full text |Cite
|
Sign up to set email alerts
|

Does usnic acid affect microtubules in human cancer cells?

Abstract: Usnic acid, a lichen metabolite, is known to exert antimitotic and antiproliferative activities against normal and malignant human cells. Many chemotherapy agents exert their activities by blocking cell cycle progression, inducing cell death through apoptosis. Microtubules, protein structure involved in the segregation of chromosomes during mitosis, serve as chemotherapeutical targets due to their key role in cellular division as well as apoptosis. The aim of this work was to investigate whether usnic acid aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…In was concluded that the antineoplastic activity of UA is not related to alterations in the formation and/or stabilization of microtubules. 27 The cytotoxic activity of purified lichen metabolites was evaluated by Brisdelli et al, in three human cancer cell lines included "MCF-7 (breast adenocarcinoma), HeLa (cervix adenocarcinoma) and HCT-116 (colon carcinoma)". 28 It was found that the highest cytotoxic activity against all cancer cell lines analyzed was higher than 25mM when compared with the other lichen.…”
Section: Usnic Acid As Cytotoxic and Anti-proliferative Agentmentioning
confidence: 99%
“…In was concluded that the antineoplastic activity of UA is not related to alterations in the formation and/or stabilization of microtubules. 27 The cytotoxic activity of purified lichen metabolites was evaluated by Brisdelli et al, in three human cancer cell lines included "MCF-7 (breast adenocarcinoma), HeLa (cervix adenocarcinoma) and HCT-116 (colon carcinoma)". 28 It was found that the highest cytotoxic activity against all cancer cell lines analyzed was higher than 25mM when compared with the other lichen.…”
Section: Usnic Acid As Cytotoxic and Anti-proliferative Agentmentioning
confidence: 99%
“…A study on the effects of usnic acid on MCF-7 (estrogen dependent, wild-type p53) indicated no morphological changes in microtubules or increase in the mitotic index. This suggests that the antineoplastic activity of usnic acid is not related to alterations in the formation and/or stabilization of microtubules (O'Neill et al 2010).…”
Section: Usnic Acidmentioning
confidence: 92%
“…Liu et al (2010) and Ren et al (2009) also identified a mitochondriamediated apoptosis pathway by showing changes in the ratio of Bax/Bcl-2 proteins after treatment with retigeric acid B or acetone extract of L. zahlbruckneri, respectively. At least for usnic acid, alterations in the formation and/or stabilization of microtubules are not responsible for the antimitotic and antiproliferative activities (O'Neill et al 2010). …”
Section: Lichens As Cytotoxic Chemotherapeutic Agentsmentioning
confidence: 99%